(3GdJehjd GdYGe (B:s (3GdeONd GdEONGQj hGdVQjHj, GdeONd GdESdGej hGdeONd GdOhdj (B/s - (3YHO GdYRjR, SejQ eMeOs ((3GdEScfOQjI(B: s (3ecJHI heWHYI GdETYGY GdafjI(B, s, 1998)
(3GdeONd GdEONGQj hGdVQjHj(B- (3GdeONd GdESdGej aj Jehjd GdJfejI(B- (3eONd GdJehjd GdOhdj ddJfejIs
Keywords: (3GdJfejI GdGbJUGOjI(B- (3GdJehjds; (3GdeGdjI GdYGeI(B- (3Gdabg GdESdGejs